A Parent Treatment Program for Preschoolers With Obesity: A Randomized Controlled Trial - Anna Ek; Kathryn Chamberlain; Kimmo Sorjonen; Ulf Hammar; Mahnoush Etminan Malek; Pernilla Sandvik; Maria Somaraki; Jonna Nyman; Louise Lindberg; Karin Nordin; Jan Ejderhamn; Philip A. Fisher; et al. (2019)
Early obesity treatment seems to be the most effective, but few treatments exist. In this study, we examine the effectiveness of a parent-only treatment program with and without booster sessions (Booster or No Booster) focusing on parenting practices and standard treatment (ST).Families of children 4 to 6 years of age with obesity were recruited from 68 child care centers in Stockholm County and randomly assigned to a parent-only program (10 weeks) with or without boosters (9 months) or to ST. Treatment effects on primary outcomes (BMI z score) and secondary outcomes (BMI and waist circumference) during a 12-month period were examined with linear mixed models. The influence of sociodemographic factors was examined by 3-way interactions. The clinically significant change in BMI z score (-0.5) was assessed with risk ratios.A total of 174 children (mean age: 5.3 years [SD = 0.8]; BMI z score: 3.0 [SD = 0.6], 56% girls) and their parents (60% foreign background; 39% university degree) were included in the analysis (Booster, n = 44; No Booster, n = 43; ST, n = 87). After 12 months, children in the parent-only treatment had a greater reduction in their BMI z score (0.30; 95% confidence interval [CI]: -0.45 to -0.15) compared with ST (0.07; 95% CI: -0.19 to 0.05). Comparing all 3 groups, improvements in weight status were only seen for the Booster group (-0.54; 95% CI: -0.77 to -0.30). The Booster group was 4.8 times (95% CI: 2.4 to 9.6) more likely to reach a clinically significant reduction of ≥0.5 of the BMI z score compared with ST.A parent-only treatment with boosters outperformed standard care for obesity in preschoolers.